Recycled Plastic Waste in Structural Concrete: Performance Assessment and Pathways for Sustainable Construction - Sapna Verma (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Plastic waste is one of the most persistent environmental pollutants worldwide, with an annual global production exceeding 390 million tons. Incorporating recycled plastic into concrete offers a dual benefit—reducing plastic pollution and conserving natural aggregates. This paper presents a comprehensive review and experimental synthesis of the mechanical, durability, thermal, and workability properties of concrete mixes containing 0–20% recycled plastic aggregates by weight of fine or coarse aggregate. Laboratory results reveal that while compressive strength decreases from 42 MPa (0% plastic) to 29 MPa (20% plastic), flexural strength improves from 5.1 MPa to 7.4 MPa at similar replacement levels. Durability performance shows significant gains: chloride penetration depth is reduced by 38%, carbonation depth decreases by 32%, and freeze–thaw weight loss drops by 40% compared to conventional concrete. Plastic-modified mixes also exhibit a 35% lower thermal conductivity, enhancing energy efficiency in building envelopes. These findings underscore the potential of recycled plastic as a sustainable construction material, while highlighting the need for long-term leaching studies, mix optimization, and codified testing standards before large-scale deployment. DOI: https://doi.org/10.17762/ijisae.v12i23s.7865